2022
DOI: 10.4103/jpbs.jpbs_819_21
|View full text |Cite
|
Sign up to set email alerts
|

An In vitro Study to Determine the Antibacterial Activity of Chlorhexidine and Herbal Mouthrinses against Enterococcus faecalis

Abstract: Background: Oral diseases have a strong history of treating by natural remedies. Chemical plaque reduction techniques, including dental mouthwashes, are intriguing because they can help patients who are unable to maintain appropriate mechanical plaque management. They are a less technically difficult alternative to mechanical control. Aim: This study aimed to compare the antibacterial efficacy of an herbal and 0.2% chlorhexidine gluconate mouthrinse against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
0
0
Order By: Relevance
“…Additionally, a meta-analysis by Costa et al [ 19 ] revealed that using mouthwashes that contained a chlorhexidine base reduced the probing depth in patients with chronic periodontitis. This is in addition to several other studies, in which chlorhexidine gluconate was shown to be effective in reducing the virulence of bacteria and yeasts such as E. faecalis and C. albicans [ 14 , 20 , 21 ]. The long-term use of antiseptics may produce a resistance in vivo, due to the exposure to sublethal concentrations that has arisen over the last century [ 22 ].…”
Section: Introductionsupporting
confidence: 59%
“…Additionally, a meta-analysis by Costa et al [ 19 ] revealed that using mouthwashes that contained a chlorhexidine base reduced the probing depth in patients with chronic periodontitis. This is in addition to several other studies, in which chlorhexidine gluconate was shown to be effective in reducing the virulence of bacteria and yeasts such as E. faecalis and C. albicans [ 14 , 20 , 21 ]. The long-term use of antiseptics may produce a resistance in vivo, due to the exposure to sublethal concentrations that has arisen over the last century [ 22 ].…”
Section: Introductionsupporting
confidence: 59%
“…Various authors have used Chlorhexidine mouth rinse on diverse oral bacteria and derived similar inferences. 35 , 36 Despite the high efficacy of 0.2% GI and 0.2% CHX in reducing microbial levels from baseline to 12 th hr study time period, the 0.1% Turmeric mouth rinse group also exhibited a decline in microbial colonies during the 6 th to 12 th hr interval. Comparable decline in growth of mature biofilm was documented in a research conducted by Bomdyal, et al 37 (2017) where the antimicrobial properties of turmeric against periodontopathogens were evident at the end of 48 hours.…”
Section: Discussionmentioning
confidence: 97%